Analysis and design of single-span integral bridge members using strut-and-tie modeling approach - Banerjee, Supriya; Saini, Kusum; Matsagar, Vasant A. (Journal of Structural Engineering, 2024)
The use of Carbon Fiber-Reinforced Polymers (CFRP) for reinforcing and prestressing concrete structures is a promising alternative in the infrastructure industry. Particularly, prestressed concrete members reinforced with such polymeric materials are becoming popular to evade corrosion-related issues. The conventional simply supported bridge requires bearings and expansion joints for various load transfers, mandating regular maintenance and protection from corrosion. The corrosion-related distress and additional joints directly or indirectly reduce the bridge life and increase the cost as well as maintenance activities. To avoid such challenges, the present study proposes the design of an integral bridge with reinforced and prestressed fiber-reinforced composite tendons alternative to the traditional simply supported bridge reinforced with corrosion-prone steel rebars. Herein, the Strut-and-Tie Modeling (STM) approach is followed for the analysis of the integral bridge members. Furthermore, the design of the integral bridge based on the STM approach is compared with the traditional limit state design approach. A full-scale three-dimensional (3D) Finite Element (FE) model of a CFRP composite-reinforced single-span integral bridge is developed. Stress field analysis is performed corresponding to Ultimate Limit State (ULS) combinations as per the EN 1990 Eurocode. Also, topology optimization of an idealized portal frame of the bridge is performed for the applied vertical loading on the structure. The optimized truss topology has proven helpful in reducing computational cost and time requirements using the STM approach.